2010
DOI: 10.1007/s10921-010-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hardness on Eddy Current Residual Stress Profiling in Shot-Peened Nickel Alloys

Abstract: Recent research results indicate that eddy current conductivity measurements can be exploited for nondestructive evaluation of subsurface residual stresses in surfacetreated nickel-base superalloy components. According to this approach, first the depth-dependent electric conductivity profile is calculated from the measured frequency-dependent apparent eddy current conductivity spectrum. Then, the residual stress depth profile is calculated from the conductivity profile based on the piezoresistivity coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…4. The results clearly confirm that RR1000 exhibits the general monotonic trend between the hardness and the conductivity, as observed in the previous research works [4][5][6]. As mentioned earlier, the literature attributes the hardness influence of conductivity in nickel-based alloys on J'' and G phase precipitates.…”
Section: Electrical Conductivitysupporting
confidence: 90%
See 2 more Smart Citations
“…4. The results clearly confirm that RR1000 exhibits the general monotonic trend between the hardness and the conductivity, as observed in the previous research works [4][5][6]. As mentioned earlier, the literature attributes the hardness influence of conductivity in nickel-based alloys on J'' and G phase precipitates.…”
Section: Electrical Conductivitysupporting
confidence: 90%
“…In a recent study, Pereira et al [6] compared the hardness and the conductivity of IN718 with the lattice constant to examine the underlying mechanisms. It is consistently concluded from these research works [4][5][6] that the electrical conductivity of the material is influenced significantly by the evolution of precipitates during thermal aging. Formation and subsequent coarsening of J'' precipitates removes solute atoms from the matrix, causing a reduction in electron scattering and an increase in conductivity.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Eddy current (EC) method has been studied regarding its potential for measuring subsurface and surface residual stress based on the empirical piezoresistivity effect [2][3][4][5][6]. It has been reported that shot peening-induced change in conductivity measured using the EC method is affected by the microstructure of the material [5,[7][8].The objective of this study is to understand how the microstructure of the samples affect the eddy current measurements. This paper talks about the quantification of size and concentration of the secondary phase precipitates (γ', γ", δ and metal carbides) and their effects on the conductivity of Inconel 718.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant potential of EC, several challenges have been identified against development of the measurement technique for residual stress characterization. In particular, it has been found in recent studies that the EC responses of Inconel 718 to shot peening depend on the underlying microstructures [5][6][7][8]. These findings indicate the confounding effects of metallurgical factors on EC residual stress measurements, and raised doubts about the applicability of the empirical piezoresistivity relationship to shotpeened surfaces without modification or compensation for the competing effects of peening-induced changes in the material conditions.…”
Section: Introductionmentioning
confidence: 99%